Children's toy or grown-ups' gamble? LEGO sets as an alternative investment. Issue 5 (1st December 2020) - Shanaev, Savva; Shimkus, Nikita; Ghimire, Binam; Sharma, Satish
Abstract : Purpose: The purpose of this paper is to study LEGO sets as a potential alternative asset class. An exhaustive sample of 10, 588 sets is used to generate inferences regarding long-term LEGO performance, its diversification benefits and return determinants. Design/methodology/approach: LEGO set performance is studied in terms of equal- and value-weighted portfolios, sorts based on set characteristics and cross-sectional regressions. Findings: Over 1966–2018, LEGO value-weighted index accounted for survivorship bias enjoys 1.20% inflation-adjusted return per annum, well below 5.54% for equities. However, the defensive properties of LEGO are considerable, as including 5%–25% of LEGO in a diversified portfolio is beneficial for investors with varying levels of risk aversion. LEGO secondary market is relatively internationalised, with investors from larger economies, countries with higher per capita incomes and less income inequality are shown to trade LEGO more actively. Practical implications: LEGO investors derive non-pecuniary utility that is separable from their risk-return profile. LEGO is not exposed to any of the Fama-French factors, however, set-specific size and value effects are also well-pronounced on the LEGO market, with smaller sets and sets with lower price-to-piece ratio exhibiting higher yields. Older sets are also enjoying higher returns, demonstrating a liquidity effect. Originality/value: This is the first study to investigate the investment properties of LEGO as an alternative asset class from micro- and macro-financial perspectives that overcomes many survivorship bias limitations prevalent in earlier research. LEGO trading is shown to be an important source of valuable data to enable original robustness checks for prominent theoretical concepts from asset pricing and behavioural finance literature.